1996
DOI: 10.1111/j.1468-5973.1996.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Peoples' Perception and Response to Floodings: The Bangladesh Experience

Abstract: Bangladesh, a test case of disaster management, has been continuously internalizing lessons learned by the people, the bureaucracy and non-governmental organizations (NGOs), after successfully responding to major natural disasters, particularly floods. The unprecedented flood of 1988 was a great educator to almost all stakeholders in Bangladesh. Since then, it has improved its capacity to cope with disasters despite some failures in its management of the macro-economy and governance. Credit goes mostly to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In order to meet the demands of an exceptional incident, conventional rules that are enshrined in Standard Operating Procedures (SOPs) had to be circumvented or 'broken'. Whilst this is not a new finding (see Auf der Heide, 1989;Smith and Dowell, 2000), this study has shown that such adaptations can result in problems, such as misunderstandings with other agencies which can jeopardize the incident response. Mendonça et al (2007) also note that both organisational and individual level improvisation demand high levels of communication.…”
Section: The Context Of the Situation Forced Responding Agencies Awaymentioning
confidence: 78%
See 3 more Smart Citations
“…In order to meet the demands of an exceptional incident, conventional rules that are enshrined in Standard Operating Procedures (SOPs) had to be circumvented or 'broken'. Whilst this is not a new finding (see Auf der Heide, 1989;Smith and Dowell, 2000), this study has shown that such adaptations can result in problems, such as misunderstandings with other agencies which can jeopardize the incident response. Mendonça et al (2007) also note that both organisational and individual level improvisation demand high levels of communication.…”
Section: The Context Of the Situation Forced Responding Agencies Awaymentioning
confidence: 78%
“…Despite these drawbacks, it is felt that the case study presented here provides a useful description of the problems associated with multi-agency response work. Additionally, the method adopted for this study closely resembles that of Smith and Dowell's (2000) investigation of a railway accident.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physiographically, landmass of Bangladesh exhibits flood plains that renders the nation at risk of periodic flooding. Three mighty rivers, the Brahmaputra, Ganges and Meghna and their tributaries and distributaries contribute to the genesis of flood plain in their respective catchment areas and floods of varying magnitude occur on a regular basis due to low elevated flood plains within these catchments [8][9][10][11]. In the last 100 years, floods resulted over 50,000 people deaths, left nearly 32 million homeless and affected more than 300 million people in Bangladesh [12].…”
Section: Introductionmentioning
confidence: 99%